The Degree of Availability of Citizenship Values in Kindergarten Curricula in the Kingdom of Saudi Arabia - Youssif, Ahmed Al-Shawadfy; Al-Wahsh, Hala Mokhtar; Darwish, Safaa Mostafa (Journal of Ecohumanism, 2024)
The current study aimed to determine the degree of availability of citizenship values in kindergarten curricula in the Kingdom of Saudi Arabia. To achieve the objectives of the study, the researcher developed a questionnaire that included (24) items. The researcher also designed a card to record the content of the Kindergarten National Unity Book in light of the dimensions of digital citizenship. In the results of the study, the availability of citizenship values in the content of a national curriculum for kindergartens in the Kingdom of Saudi Arabia was at a very high rate, amounting to (5) values: equality, justice, loyalty to the homeland, participation, freedom, and social responsibility. The degree of availability of equality and justice came at a rate of (42.5). % of the total values of citizenship in the content of a national curriculum for kindergartens in the Kingdom of Saudi Arabia, the degree of availability of loyalty to the homeland came in at (11.7%). The degree of availability of participation in the content of a national curriculum came in at (12.64%). The degree of availability of freedom in the content of a national curriculum came in at (12.64%). 15.8%) The degree of availability of social responsibility in the content of a national curriculum for kindergartens in the Kingdom of Saudi Arabia came at a rate of (17.38%) of the total values of citizenship in the content of a national curriculum for kindergartens in the Kingdom of Saudi Arabia. The researcher recommended the necessity of benefiting from the list of citizenship values and their indicators in the content of the unit National kindergarten curriculum.